A religious history of the American people - Ahlstrom, Sydney E. (New Haven : Yale University Press, 1972)
Provides a comprehensive survey of religious beliefs, practices, and trends in America and includes background information on secular movement and influences.
American religious history in the post-Protestant era -- Western Catholicism -- The church in New Spain -- The church in New France -- The Reformation -- The Reformation in Great Britain and the age of Puritanism -- Empire, commerce, and religion : a survey of early colonization -- The rise and flowering of the Puritan spirit -- The holy commonwealths of New England -- Tensions in the New England way -- Religious diversity in Rhode Island -- Early Protestantism in the Southern colonies -- The middle colonies : Dutch, Puritans, and Quakers -- The extension of Anglicanism -- The German sects and the rise of pietism -- The German Reformed and Lutheran churches -- The shaping of colonial Presbyterianism -- The Great Awakening in New England -- Jonathan Edwards and the renewal of New England theology -- Evangelical expansion in the South -- Roman Catholicism in the American colonies -- Provincial America and the coming of the Enlightenment -- The Revolutionary era -- The emergence of American Unitarianism -- The New England theology in democratic America -- The Second Great Awakening in New England : revival, evangelism, and reform -- The great revival in the West and the growth of the popular denominations -- Presbyterians and Congregationalists in the Old Northwest : advance and conflict -- Sectarian heyday -- The communitarian impulse -- The Atlantic migration and Lutheran crisis -- The forming of the Roman Catholic church -- The expansion of the Roman Catholic church -- Anti-Catholicism and the nativist movement -- The early growth of Judaism -- The romantic mood -- Romantic religion in New England -- Catholic movements in American Protestantism -- The high tide of humanitarian reform -- Slavery, disunion, and the churches -- The churches amid civil war and reconstruction -- The rise of the black churches -- The Southern white churches after the war -- Urban growth and the Protestant churches -- Protestantism and the later immigration -- The golden age of liberal theology -- The social gospel -- Dissent and reaction in Protestantism -- The "Americanism" crisis in the Catholic church -- The Protestant establishment and the new nativism -- Crusading Protestantism -- The little war and the Great War -- The twenties : from the armistice to the crash -- The thirties : from the crash to Pearl Harbor -- Neo-orthodoxy and social crisis -- World War II and the postwar revival -- Twentieth-century Judaism -- The ancient Eastern churches in America -- Roman Catholicism in the twentieth century -- Harmonial religion since the later nineteenth century -- Piety for the age of Aquarius : theosophy, occultism, and non-Western religion -- Black religion in the twentieth century -- The turbulent sixties.
Includes bibliographical references (pages 1097-1128) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: United States -- Religion; United States -- Religion; États-Unis -- Religion; RELIGION -- History; TRAVEL -- Special Interest -- Religious; Religion; United States; United States -- Church history; Religion; Geschichte; Kirchengeschichte; USA; Godsdiensten; Religiao (Historia)